2013
DOI: 10.3171/2013.5.focus13147
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal endoscopic approach to the pediatric craniovertebral junction and rostral cervical spine: case series and literature review

Abstract: The endoscopic transnasal approach to the rostral pediatric spine and craniovertebral junction is a relatively new technique that provides an alternative to the traditional transoral approach to the anterior pediatric spine. In this case series, the authors provide 2 additional examples of patients undergoing endoscopic transnasal odontoidectomies for ventral decompression of the spinal cord. Both patients would have required transection of the palate to undergo an effective transoral operation, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Serious complications documented in previous case reports and clinical series 3,[9][10][11][12]14,16,17,25,26,30,31,34 are infrequent. However, maintaining the integrity of the dura mater is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Serious complications documented in previous case reports and clinical series 3,[9][10][11][12]14,16,17,25,26,30,31,34 are infrequent. However, maintaining the integrity of the dura mater is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 3,[9][10][11][12]14,16,17,22,25,26,30,31,34 have demonstrated the effectiveness and feasibility of an odontoidectomy performed using an EEA and suggest the possibility of less invasiveness than with the oral or cervical approaches. In our small series there is no evidence of different neurological functional outcomes between the techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,47,55 Although these extended approaches can lead to significant enhancement of the surgical exposure, they also significantly increase surgical complexity and the depth of the operative corridor, rates of morbidities such as infections from bacterial oral flora, velopharyngeal insufficiency, hypernasal speech, nasal regurgitation, soft palate dehiscence, tongue edema, and necrosis, and the potential need for tracheotomy and nasogastric feeding tube, resulting in a longer hospital recovery time. 10,37,41,45 In the last decade, some minimally invasive endoscopic approaches, such as the EEA, 7,8,11,18,19,[21][22][23][24]26,27,29,30,[33][34][35]40,44,51 the ETA, 16,17 a combined EEA/ETA with or without the assistance of robotics, 12,13,31,32,50,54 and a transcervical approach, 53 have been adopted to address CVJ pathology. The growing number of publications in the last decade shows that the EEA can be an excellent minimal-access alternative to traditional transoral surgery and offers certain anatomical advantages.…”
Section: Discussionmentioning
confidence: 99%